Surf's up, Geronimo! - Stilton, Geronimo (New York : Scholastic, 2005)
Geronimo Stilton dreams of a quiet vacation at the beach, but ends ups at a fleabag hotel that is falling apart.
Keywords: Children's stories; Action and adventure fiction